Loop-mediated isothermal amplification assay: A novel disease diagnostics tool in sweetpotato seed quality assurance - Wanjala, Bramwel W.; Kreuze, Jan F.; McEwan, M. (Wiley, 2024)
Sweetpotato is an important food crop in global production. However, sweetoptato viruses pose a threat to sustainable agriculture and cause significant economic loss. More than 30 viruses have been reported to date, with sweet potato feathery mottle virus (SPFMV) and sweet potato chlorotic stunt virus (SPCSV) occurring frequently and in combination, causing sweetpotato virus disease. The detection of viruses directly from sweetpotato is still a challenge, and efforts are being made toward this front. Therefore, rapid detection of viruses is critical for effective control. Current diagnostic tests are not sufficiently sensitive to reliably detect viruses directly from sweetpotato and require expensive laboratory equipment and a high level of skilled experience. Loop-mediated isothermal amplification (LAMP) is sensitive and specific for both DNA/RNA amplification; it is affordable and its characteristics make it potentially suitable for on-site testing. LAMP assays have been developed for several sweetpotato viruses: SPCSV, SPFMV, and sweet potato leaf curl virus (and related sweepoviruses). Laboratory validation showed a 100% diagnostic sensitivity for all three viruses. The LAMP on-site testing results were comparable to those of polymerase chain reaction and reverse transcriptase polymerase chain reaction confirmatory laboratory tests. Interlab validation and packaging into affordable kits will ensure high adoption in sub-Saharan Africa. The LAMP assay can be used for field surveys and monitoring the phytosanitary status of pre-basic seed production in quarantine or certification program. This guarantees pathogen-free planting material enters the seed system. We discuss opportunities for LAMP as a diagnostic assay for the rapid detection of sweetpotato viruses and its adoption as a quality control system for planting materials. Sweet potato feathery mottle virus (SPFMV), sweet potato chlorotic stunt virus (SPCSV), and sweet potato leaf curl virus (SPLCV) are the most common viruses known to cause disease in sweetpotato. Field deployable loop-mediated isothermal amplification (LAMP) assay for the rapid detection of SPFMV, SPCSV, and SPLCV. Adoption of the LAMP assay by field inspectors for field surveys and monitoring the phytosanitary status of pre-basic seed production in quarantine or certification programs.